Reproductive success of orchids at the northern border of their distribution areas (North-East of European Russia) - Irina A. Kirillova; Dmitriy V. Kirillov (Nature Conservation Research: Заповедная наука, 2021)
The Orchidaceae is one of the most interesting angiosperm families due to their biology and ecology. However, our knowledge about northern orchids, especially about several aspects of their reproduction biology, is still scarce. This study presents data on reproduction biology of 13 orchid species from the Republic of Komi, situated at the northern border of the orchids' distribution areas. Data on flower number, fruit set, seed morphometry and seed number are presented. The volume of the largest and smallest seeds differs in the study area by 10 times (from 1.2 × 10-3 mm3 in Malaxis monophyllos to 14.2 × 10-3 mm3 in Cypripedium guttatum). The seed shape is determined by the habitat type. Similarly to previous studies, we found that deceptive orchids have lower rates of fruit set, compared to the nectar-rewarding ones. For deceptive orchids, the low fruit set is compensated by the larger number of seeds per fruit, compared to the nectar-rewarding species. The fruit set is correlated positively with the flower number in the deceptive orchids. Moreover, the fruit set rate might also depend on the habitat characteristics, e.g. the canopy closure. The final indicator of a successful reproductive process is the number of emerged and established young plants. This parameter differs between species with different structures of storage organs. We found the lowest proportion of juvenile individuals in rhizome species (2.7–8.9%), in which the low seed reproduction is compensated by the ability to vegetative reproduction and long persistence of clones. In orchids with root-stem tuberoids, the only way of reproduction is seed reproduction. Populations of these species have a higher proportion of juvenile plants (11.8–19.9%). We found similar adaptations to maintain the maximal seed reproduction rate at the northern border of distribution areas in two root-stem tuberoid orchid species (nectar-rewarding Platanthera bifolia and deceptive Dactylorhiza incarnata). The adaptations include an increase in seed number per fruit and a decrease in the seed size in comparison to the southern part of the distribution areas of these species.